Ten Years of Critical Tourism Studies: Reflections on the Road Less Traveled - Nigel Morgan (Tourism Analysis, 2018)
This introduction to the Special Issue describes and reviews the development of the Critical Tourism Studies Network and its unfolding values-led humanist and transformative perspective. It defines its philosophical roots and its inquiry–learning–action nexus, before briefly outlining the evolution and trajectory of tourism studies as a field of inquiry to provide context for the critical turn. The introduction concludes by summarizing the approaches and methodologies employed in the six articles of the collection, all of which provide both insights into the current state of critical tourism studies and glimpses of some of the challenges that lie ahead for the field of tourism studies.